Analisis Kesalahan Berbahasa pada Aspek Nahwu dalam Pembelajaran Insya’ oleh Siswa Tingkat Madrasah Tsanawiyah - Fitria, Faiza; Maliyanah, Alya Afifah; Sabila, Anis Nurma (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2024)
Language is an important thing in communication between individuals, both in oral and written form. However, it cannot be denied that language errors often occur in every language activity. In learning a second language, language errors can be experienced by students due to a lack of grammatical mastery especially in the aspect of word meaning which is very different from their first language. This research is a qualitative descriptive research that aims to analyze language errors in the nahwu aspect in: (1) gender; (2) pronoun (dhamir); (3) phrases; and (4) vocabulary (mufradat) that occurs in insya' learning by students in Arabic extracurricular classes at MTs Almaarif 01 Singosari. Through an analysis of language errors in the nahwu aspect in the students' essays, in general it was found that several nahwu errors included mistakes in the use of gender, pronouns, phrases, and vocabulary. There were 13 errors (25%) in using gender, 16 errors (30.77%) in using dhamir, 11 mistakes in using phrases (21.15%), and 12 mistakes in using mufradat (23, 08%).